Effect of Corporate Governance on Dividend Policy of Nepalese Insurance Companies - Pokhrel, Sandesh; Khadka, Sewak; Acharya, Shrutee; Thapa, Smita; Thapa, Subha (Nepalese Journal of Business, 2024)
This study investigates the effect of corporate governance on dividend policy of Nepalese insurance companies. Dividend payout ratio and dividend per share are the dependent variables. Similarly, board size, female directors, number of independent directors, operating expenses and total asset are selected as independent variables. The study is based on secondary data of 15 Nepalese insurance companies with 102 observations for the period from 2013/14 to 2021/22. The data were collected from the annual reports of respective insurance companies. The correlation coefficients and regression models are estimated to test the significant and importance of different corporate governance variables on the dividend policy of Nepalese insurance companies. This study shows that the board size has a positive impact on dividend payout ratio and dividend per share. It indicates that increase in the number of board members leads to increase in dividend payout ratio and dividend per share in Nepalese insurance companies. Likewise, female director has a positive impact on dividend payout ratio and dividend per share. This implies that higher the number of female directors in the board of a company, higher would be the dividend payout ratio and dividend per share. Similarly, the number of independent directors has a positive impact on dividend payout ratio and dividend per share. It means that the increase in number of independent directors leads to increase in dividend payout ratio and dividend per share. Moreover, operating expenses has a positive impact on dividend payout ratio and dividend per share. This indicates that higher the operating expense ratio, higher would be the dividend payout ratio and dividend per share. In addition, total assets have a positive impact on dividend payout ratio and dividend per share. It indicates that increase in the total assets leads to increase in dividend payout ratio and dividend per share in Nepalese insurance companies.